Human Resource Strategies for Enhancing Creative Product Competitiveness in the Digital Era - Marwati, Fithri Setya; Istiatin (The Indonesian Institute of Science and Technology Research, 2025)
This study addresses the challenges faced by Human Resources (HR) in micro, small, and medium enterprises (MSMEs) in adapting to digital advancements, particularly in leveraging social media for marketing. The research focuses on Mom Fithri Brass & Copper Craft and Fried Shallot business located in Cepogo, Boyolali, where HR capabilities in digital marketing remain limited despite its vast potential. This study aims to analyze the role of Human Resource Management (HRM) in enhancing the development of creative economy products in the digital era. A descriptive qualitative approach was employed, using observation, interviews, and documentation as data collection methods. The population consisted of 30 employees and one business owner, with the sample being the business owner. Findings reveal that HRM plays a pivotal role in improving the digital competencies of human resources, which in turn fosters innovation and enhances product development. The training implemented significantly improved digital marketing knowledge and skills, enabling the MSMEs to become more competitive in the global marketplace. Moreover, HR demonstrated increased creativity in utilizing social media to expand market reach and visibility of their products.